Giant Right Atrial Thrombus associated with Tunneled Cuffed Hemodialysis Catheter: A Case of Successful Treatment with Thrombolytic Agent and Anticoagulant - Young Jin Song; Young-Ki Lee; Sun Ryoung Choi; Ji-Hyun Kim; Sun Woo Kim; Jung-Woo Noh (Kosin Medical Journal, 2013)
There are a variety of tunneled cuffed hemodialysis catheter-related complications including infection, thrombus formation, and catheter dysfunction. Catheter-related thrombus in right atrium is a rare complication and treatment guideline for atrial thrombus does not exist. A 3.0×2.8 cm sized giant atrial thrombus was found in a 35-year-old female hemodialysis patient. She was treated with catheter removal, thrombolysis and anticoagulation therapy. Size of atrial thrombus was gradually decreased and left ventricular systolic function was clearly improved after treatment. We experienced and reported a case of giant right atrial thrombus associated with tunneled cuffed hemodialysis catheter that was successful treated with thrombolytic agent and anticoagulant.